1997
DOI: 10.1046/j.1365-2141.1997.102652.x
|View full text |Cite
|
Sign up to set email alerts
|

Comparative analysis of the impact of risk profile and of drug therapy on survival in CML using Sokal's index and a new score

Abstract: Summary. Survival times in chronic myeloid leukaemia (CML) may vary widely depending on the risk profiles of patients. This fact is frequently not, or not sufficiently, considered in evaluating survival in CML, and some studies do not report risk profiles. Therefore we analysed the relative impact of risk profile and therapy on survival using the median survival times of therapy groups and of risk groups of the three-arm randomized German CML Study I (interferon alpha v hydroxyurea v busulphan; median survival… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
30
0

Year Published

2000
2000
2012
2012

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(30 citation statements)
references
References 17 publications
0
30
0
Order By: Relevance
“…Unlike the most popular HU, which is a structurally simple antimetabolite that interferes with DNA synthesis by inhibiting ribonucleotide reductase activity (35), a conflict of opinions has emerged regarding the corresponding pathogenetic model for IFN. IFN therapy facilitates an induction of a major hematologic remission in about 80% of patients and a complete cytogenetic response in a few patients, resulting in significantly prolonged survival (39,40). Based on experimental data, two possibilities of IFN actions on the CML bone marrow are currently under discussion.…”
Section: Discussionmentioning
confidence: 99%
“…Unlike the most popular HU, which is a structurally simple antimetabolite that interferes with DNA synthesis by inhibiting ribonucleotide reductase activity (35), a conflict of opinions has emerged regarding the corresponding pathogenetic model for IFN. IFN therapy facilitates an induction of a major hematologic remission in about 80% of patients and a complete cytogenetic response in a few patients, resulting in significantly prolonged survival (39,40). Based on experimental data, two possibilities of IFN actions on the CML bone marrow are currently under discussion.…”
Section: Discussionmentioning
confidence: 99%
“…Many randomized studies now state their proportion of Sokal scores to aid in interpretation of results. One paper reported that disease characteristics, as measured by risk status, was a more powerful predictor of survival than therapy received, by a factor of two (Hehlmann et al, 1997). The Sokal index is typical of the other prognostic scales and uses baseline patient and disease characteristics to calculate a hazard ratio for death.…”
Section: Prognostic Features Of Chronic Phasementioning
confidence: 99%
“…Investigators have proposed new prognostic scales that more accurately predict survival after interferon-a (IFN) therapy (Hehlmann et al, 1994(Hehlmann et al, , 1997Mahon et al, 1998;Sacchi et al, 1998). The bestvalidated scale was published by Hasford et al (1998) and considers patient age, platelet count, peripheral blast count, spleen size, eosinophils and basophils when calculating risk.…”
Section: Prognostic Features Of Chronic Phasementioning
confidence: 99%
“…5 Hehlmann and colleagues report that stratification according to risk group has a greater effect on survival than treatment allocation in patients receiving IFN-␣, hydroxyurea or busulfan. 26 This suggests that risk profile is an important potential confounder in comparisons of treatment and should be taken into account, preferably through the use of randomisation in the context of direct comparisons.…”
Section: Risk Scoresmentioning
confidence: 99%
“…24 Both Sokal and Hasford scores have been shown to be predictors of survival. 5,[25][26] The Benelux CML Study Group reports that the Sokal score is discriminatory for survival in patients receiving hydroxyurea, but not for patients receiving IFN-␣. 5 Hehlmann and colleagues report that stratification according to risk group has a greater effect on survival than treatment allocation in patients receiving IFN-␣, hydroxyurea or busulfan.…”
Section: Risk Scoresmentioning
confidence: 99%